Mapping the Rapid Decline of the Intertidal Wetlands of China Over the Past Half Century Based on Remote Sensing - Song, Song; Wu, Zhifeng; Wang, Yuefeng; Cao, Zheng; He, Zhenyu; Su, Yongsong (Frontiers in Earth Science, 2020)
Intertidal wetland located at the interface of the continent and ocean, provides significant support to human society. As the largest developing country and the 2nd-biggest economy among the world, intertidal wetland along China coast have been exposed to climate change and over-exploitation since decades. Despite its ecological and economic significance, the distribution and variation of the intertidal wetland remains unknown. In this study, based on the multiple temporal remote sensing archive accumulated since 1970s, we detected the dynamics of intertidal wetland along Chinese coast at 30m spatial resolution with a time interval of 20 years, over the course of four decades (1970s-2015). The main objectives of this study lie in, (1) examine the intertidal wetland extent distribution and variation in temporal and spatial aspects; (2) discuss the main driving force of the intertidal wetland dynamics; (3) suggest to future research and management. The results suggested that the extent of intertidal wetland declined substantially during the last four decades, from 7848 km2 in 1970s, to 6017 km2 in 1995, and finally to 4895 km2 in 2015. Averagely the intertidal wetland stretched 0.22 km in width along the coast, and about 40% of the extent of intertidal wetland was contributed by Jiangsu and Shandong in 2015. Shrinkage width and seaward migration of the intertidal wetland was primarily detected, due to the intensive land reclamation. This study improved our understanding to these vulnerable but valuable transition zone of intertidal wetland, and necessitates the high priority of intertidal wetland conservation toward the sustainable future.